Collateral Imbalances in Intra-European Trade? - Arne J. Nagengast; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2014)
Abstract One of the main stylised facts that has emerged from the recent literature on global value chains is that bilateral trade imbalances in gross terms can differ substantially from those measured in value added terms. However, the factors underlying the extent and sign of the differences between the two measures have so far not been investigated. Here, we propose a novel decomposition of bilateral gross trade balances that accounts for the differences between gross and value added concepts. The bilateral analysis contributes conceptually to the literature on double counting in trade by identifying the trade flow in which value added is actually recorded for the first time in international trade statistics. We apply our decomposition framework to the development of intra-EU-27 trade balances from 1995-2011 and show that a growing share of intra-EU bilateral trade balances is due to demand in countries other than the two direct trading partners.
Keywords: F1; F2; C67; R15; 330; trade balances; global value chains; vertical specialisation; value added; input-output tables